"Go", "No Go, " or "Where to Go"; does microbiota dictate T cell exhaustion, programming, and HIV persistence?. Issue 4 (July 2021) - Shukla, Sudhanshu; Kumari, Sangeeta; Bal, Saswat K.; Monaco, Daniela C.; Ribeiro, Susan Pereira; Sekaly, Rafick-Pierre; Sharma, Ashish Arunkumar
Abstract : Purpose of review: People living with HIV who fail to fully reconstitute CD4 + T cells after combination antiretroviral therapy therapy (i.e. immune nonresponders or INRs) have higher frequencies of exhausted T cells are enriched in a small pool of memory T cells where HIV persists and have an abundance of plasma metabolites of bacterial and host origins. Here, we review the current understanding of critical features of T cell exhaustion associated with HIV persistence; we propose to develop novel strategies to reinvigorate the effector function of exhausted T cells with the aim of purging the HIV reservoir. Recent findings: We and others have recently reported the role of microbiota and metabolites in regulating T cell homeostasis, effector function, and senescence. We have observed that bacteria of the Firmicute phyla (specifically members of the genus Lactobacilli ), associated metabolites (β-hydroxybutyrate family), and bile acids can promote regulatory T cell differentiation in INRs with a senescent peripheral blood gene expression profile. Summary: The cross-talk between immune cells and gut microbes at the intestinal mucosa (a major effector site of the mucosal immune response), regulates the priming, proliferation, and differentiation of local and distant immune responses. This cross-talk via the production of major metabolite families (like serum amyloid A, polysaccharide A, and aryl hydrocarbon receptor ligands) plays a key role in maintaining immune homeostasis. HIV infection/persistence leads to gut dysbiosis/microbial translocation, resulting in the local and systemic dissemination of microbes. The ensuing increase in immune cell-microbiome (including pathogens) interaction promotes heightened inflammatory responses and is implicated in regulating innate/adaptive immune effector differentiation cascades that drive HIV persistence. The exact role of the microbiota and associated metabolites in regulating T cell- mediated effector functions that can restrict HIV persistence continue to be the subject of on-going studies and are reviewed here.